The Effect of Digitalization on Employee Performance on PT. Ilham Jaya Cabindo Jakarta - Wijaya, Shabrina Risma; Junengsih, Junengsih; Imanuddin, Kaffah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The purpose of this study is to determine the effect of digitalization on the performance of PT. Ilham Jaya Cabindo Jakarta. This study used quantitative descriptive methods with data collection techniques through the distribution of questionnaires, and library data. In this study using a saturated sampling method used a total of 48 employees of PT. Ilham Jaya Cabindo Jakarta, using simple linear regression data analysis techniques. The results of this study show that there is an influence between digitalization on the performance of PT. Ilham Jaya Cabindo Jakarta has a moderate positive effect and has an influence contribution of 16.3% on employee performance variables. The results of this study are expected to contribute to future research.